Bioactive compounds from plant origin : extraction, applications, and potential health benefits - Suleria, Hafiz; Barrow, Colin J. (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2019)
"This new volume explores the importance of phytochemicals from plants in therapeutics and human health. Its focus is on the extraction of bioactive compounds and their applications in human health. Natural products and their bioactive compounds are increasingly utilized in preventive and therapeutic medication as well as for the production of pharmaceutical supplements and more recently as food additives to increase the functionality of foods. The first section of the volume describes recent advances in the extraction of bioactive compounds from various sources. It looks at advanced extraction techniques such as enzyme-assisted, microwave-assisted, ultrasound-assisted, pressurized liquid extraction, and supercritical extraction techniques, which are described in detail. Part 2, on bioactive compounds and health claims, covers the roles of different bioactive compounds and their health-promoting potential for lifestyle diseases. The incorporation of functional food, nutraceuticals, and bioactives in daily diets helps to prevent the progression of chronic disorders. This section explains the botany, physical characteristics, uniqueness, uses, distribution, importance, phytochemistry, traditional importance, nutritional importance, bioactivities, and future trends of different functional foods. Functional foods, beyond providing basic nutrition, may offer a potentially positive effect on health and may offer cures for various disease conditions, such as metabolic disorders, cancer, and chronic inflammatory reactions. Bioactive Compounds from Plant Origins: Extraction, Applications, and Potential Health Benefits will be useful for faculty, students, and researchers as well as professionals working in the food, nutraceutical, and herbal industries. Key features: Compares conventional vs. novel methods for the extraction of bioactive molecules; Describes several green extraction techniques Explores phytochemicals from fruit wastes for sustainable poultry production; Considers the various health benefits of bioactive compounds from various plants, including garlic, persimmon, grapes, etc."--
OCLC-licensed vendor bibliographic record.
Keywords: Plant bioactive compounds -- Separation; Phytochemicals; Medicinal plants; HEALTH & FITNESS / Nutrition; SCIENCE / General; SCIENCE / Life Sciences / Botany